Signaling pathways in renal cell carcinoma - Banumathy, Gowrishankar (Landes Bioscience, 2010)
Renal cell carcinoma (RCC), the most lethal type of genitourinary cancer, is generally resistant to chemotherapy and radiation therapy. Surgical excision of the tumor at a localized stage remains the mainstay for curative therapy. A number of drugs developed in recent years have shown limited to significant efficacy in treating RCC. These drugs act by blocking critical signaling pathways associated with RCC tumor growth and survival and angiogenesis. Beyond well-validated signaling targets such as VHL, VEGFR and mTOr, additional pathways including HGF/c-MET and wnt/β-catenin have emerged as important to RCC pathogenesis. Mutations in one or more components of these signaling networks may affect tumor response to therapy. This review summarizes the state of knowledge about signaling pathways in RCC and discusses the known genetic and epigenetic alterations that underlie dysregulation of these pathways.